Reason and restitution : a theory of unjust enrichment - Webb, Charlie (Oxford legal philosophy., 2016)
While unjust enrichment is often identified as the third major branch of private law alongside contract and tort, there remains uncertainty what this body of law covers and what it's about. This book provides an account of the reasons supporting these claims and how these reasons bear on the law's application and development --